A rare case of Shewanella putrefaciens bacteremia in a patient of road traffic accident - Ritesh Ranjan; Priti Chowdhary (Wolters Kluwer Medknow Publications, 2017)
Shewanella putrefaciens rarely causes human infection. These are mostly found in environment and food stuffs. Shewanella are often found in mixed culture. It has been implicated in cellulitis, otitis media, and septicemia. It may be found in respiratory tract, urine, feces, and pleural fluid. There is no definite guideline for therapeutic option. In general, these are susceptible to various antimicrobial agents but are often resistant to penicillin and cephalothin. We report a rare case of bacteremia by S. putrefaciens in a patient of head injury with polytrauma after a road traffic accident.